The promise and perils of regulating ipso facto clauses - Sarra, JP; Payne, J; Madaus, S (Wiley, 2021)
It is common for contracts to include a clause that provides that on an event of default the counterparty has an unconditional right to terminate the contract or accelerate payment (an ipso facto clause). The regulation of ipso facto clauses has become a topic of debate in recent years with a number of jurisdictions introducing constraints on such clauses as part of broader restructuring reform packages. These jurisdictions include Germany in 2021 (as part of its implementation of the EU Restructuring Directive) and the United Kingdom in 2020. For jurisdictions introducing such constraints for the first time, there is much to learn from those, such as Canada, that have had constraints on ipso facto clauses in place for much longer. This article examines the experience in Canada alongside the constraints introduced in the United Kingdom, the EU Restructuring Directive and Germany, and identifies a series of steps that policymakers should follow when revising a regime on ipso facto clauses. Although there are a number of common themes that emerge, it is clear that different jurisdictions often make quite distinct policy choices regarding the rationale for any constraints on ipso facto clauses as well as on the specific nature and scope of the provisions. Different jurisdictions find different points of balance between the interests of individual creditors in upholding their freedom of contract and the rights of the debtor and creditors as a whole in preserving the business as a going concern. The range of choices is not per se problematic as long as they are implemented with clarity and transparency, so that debtors and creditors can bargain ex ante in the light of any legislative provisions.